Pengaruh tingkat hunian kamar terhadap pendapatan makanan dan minuman di grand aston bali beach resort tanjung benoa bali - Ni Luh Gede Marsiani; Ida Ayu Trisna Eka Putri; Fanny Maharani Suarka (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2017)
The purpose of this study is to determine the effect of room occupancy on food and beverage revenues at Grand Aston Bali Beach Resort and to know the efforts made to increase food and beverage revenues at Grand Aston Bali Beach Resort. These data were gained by observation, interview, literature study, and documentation. The data were analyzed using simple linear regression analysis, correlation, ttest, and determination with 5% significant level. Data processing by SPSS Program (Statistical Package for the Social Sciences) 21 for windows. The results indicated toward simple linear regression calculation obtained the equation Y= 33,967 + 0,097X1, which means the occupancy rate of the room (X) has a significant influence and direction of food and beverage revenues (Y). The result of correlation calculation obtained result of 0,58 with position value